ANALISA PERBEDAAN ECO-FRIENDLY ATTITUDE DAN ECO-FRIENDLY INTENTION ANTARA TURIS LOKAL DAN TURIS ASING TERHADAP GREEN - Regina Jokom; Monika Kristanti (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
The increasing concern for environmental degradation caused many people to pay more attention to the green practice in the industry including hotel. Majority of hotel chains have adopted environmental programs and labeled as green hotel. This study examines the significant differences between local tourist and foreign tourist regarding ecofriendly attitude and eco-friendly intention toward green hotel. Questionnaires were distributed to 120 localtourists and 120 foreign tourists In Juanda International Airport Surabaya. The study reveals that there are significant differences in severity of environmental problems, intention to stay, intention to spread positive word of mouth, and intention to pay extra for green hotel between local and foreign tourist.Keywords: eco-friendly attitude, eco-friendly intention, green hotel, hospitality